Pengembangan Sistem Manajemen File Terpusat Berbasis Web di Jaringan Lokal - Mantik, Joy Timoty; Yusupa , Ade (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
Managing digital documents within internal environments requires an efficient, secure, and self-sufficient system, particularly in closed networks such as those in educational institutions or offices. This study aims to design and implement a centralized file management system operating over a local area network (LAN), without relying on external services. The system is developed using PHP, MySQL, and JavaScript, and includes features such as access control, folder and file management, user activity logging, as well as notification and OTP verification via Telegram. Testing results show that all features function as expected. The system offers an effective local solution for internal document management. Future research may focus on enhancing file security and integrating advanced authentication mechanisms.